8z+11=7z+5

Simple and best practice solution for 8z+11=7z+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8z+11=7z+5 equation:


Simplifying
8z + 11 = 7z + 5

Reorder the terms:
11 + 8z = 7z + 5

Reorder the terms:
11 + 8z = 5 + 7z

Solving
11 + 8z = 5 + 7z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-7z' to each side of the equation.
11 + 8z + -7z = 5 + 7z + -7z

Combine like terms: 8z + -7z = 1z
11 + 1z = 5 + 7z + -7z

Combine like terms: 7z + -7z = 0
11 + 1z = 5 + 0
11 + 1z = 5

Add '-11' to each side of the equation.
11 + -11 + 1z = 5 + -11

Combine like terms: 11 + -11 = 0
0 + 1z = 5 + -11
1z = 5 + -11

Combine like terms: 5 + -11 = -6
1z = -6

Divide each side by '1'.
z = -6

Simplifying
z = -6

See similar equations:

| 4(12n-6)=6(-4+5n)+18n | | 2x-2.8-2.4x+2.6x-5= | | 6(-3-x)-2*x=14 | | 6sec^2(0)-2sec^2(0)= | | 4x^4+21x^2-18=0 | | -7=7-(8-a) | | Y=50+1x | | yz^2-z^2+5+3yz-3z^2+4yz= | | 16=7-(b+9) | | (x-1)(x+3)=(x+2)(x-3) | | -2*x+8=-16 | | -3x+4y=46 | | 5y-7y-6=2 | | 14=7p-ap | | 6x-6=-216 | | -6*x=42 | | 6x-4+5x=-26 | | 7y-2=6y^2 | | 5m^2-85m=0 | | x^2-17x+70=10 | | 4c^2+12x-44=0 | | 16x^2-9y^2+36y+108=0 | | Y=(-3)(4i)(7i) | | 7x-(4x+3)=1 | | [3y-2]=[26-4y] | | 16y-6=2 | | -x+9-9= | | 121x^2-16=-7 | | T*23=276 | | y=-4.9t^2+26t | | 38+2d=100 | | 82(2)= |

Equations solver categories